24 GHz CMOS Transceiver and Wireless Sensor Network for Indoor Localization - Ebelt, Randolf; Shmakov, Denys; Hamidian, Amin; Böck, Georg; Vossiek, Martin (RFIC 2013 Workshop on Radio Frequency Systems for Indoor Localization, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.24ghzc

24 GHz CMOS Transceiver with Novel T/R Switching Concept for Indoor Localization - Hamidian, Amin; Ebelt, Randolf; Shmakov, Denys; Vossiek, Martin; Zhang, Tao; Subramanian, Viswanathan; Boeck, Georg (IEEE Radio Frequency Integrated Circuits Symposium (RFIC) 2013, 2013)
This paper presents a 130 nm CMOS transceiver for 24 GHz wireless indoor localization. Due to a novel Rx/Tx switching concept RF-losses between receiver/ transmitter and antenna could be reduced and the T/R isolation was drastically improved. The measured transceiver chip achieves an output power and noise figure of >5 dBm and <6 dB, respectively with 2 mm2 total chip size. The complete transceiver consumes 16 mW in the Rx- and 26 mW in the Tx-mode. The RF-transceiver-chip was integrated with a DSP-unit and mounted on a PCB for wireless indoor localization demonstration. The measured results show a distance measurement precision in the cm-range. © 2013 IEE
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.24ghzc_4
Keywords: 130 nm CMOS; 24 GHz transceiver; localization; secondary radar

A Novel Sequential Monte Carlo Method Based Synthetic Aperture Reconstruction Approach for Real-Time 3D Wireless Local Positioning - Li, Gang; Ebelt, Randolf; Vossiek, Martin (Frequenz, 2012)
In this paper, we introduce a precise real-time 3D indoor localization concept using a combination of the MISAS (multilateral inverse synthetic aperture secondary radar) approach and SMCM (sequential Monte Carlo method). The synthetic aperture approach is a promising locating technique with effective multipath suppression. However, its practical use is restricted by the huge computational load of the reconstruction algorithms. We use a weighted-particle set-which we reduce subsequently by resampling-to represent the PDF (probability density function) instead of the highly complex, standard, grid-based approach. Simulation runs and experiments, carried out with a 5.8 GHz FMCW secondary radar system with a bandwidth of only 140 MHz, show that a robot TCP (tool center point) can be localized in 3D in the mmrange using a few hundred particles and operating in a dense multipath environment. This novel extension is a promising solution for real-time, 3D MISAS localization applications.
UnivIS-Import:2015-03-09:Pub.2012.tech.IE.LEH.anovel_9
Keywords: FMCW secondary radar; Indoor wireless positioning; Sequential Monte Carlo method; Synthetic aperture radar

An Ultra-Wideband Local Positioning System for Highly Complex Indoor Environments - Waldmann, Benjamin; Ebelt, Randolf; Vossiek, Martin; Weigel, Robert (International Conference on Localization and GNSS (ICL-GNSS) 2012, 2012)
In this paper a novel approach for a high precision local positioning radar using an ultra-wideband (UWB) technique is presented. The concept is based on the standard frequency modulated continuous wave (FMCW) radar principle combined with short pulses to fulfill the emission limits given by the official regulatory authorities. Besides the well known advantages of a FMCW radar, the proposed system implies a wide frequency bandwidth. With this concept, a high accuracy in dense multipath indoor environments can be achieved, ideally suited for 1D, 2D, and 3D localization applications for complex industrial environments. Investigations on the achievable performance of such an UWB system show very promising results and are presented within this paper. A prototype system was fabricated which operates at the center frequency of 7.5 GHz utilizing a bandwidth of 1 GHz. With the setup presented in this paper the distance between two wireless units can be measured achieving a standard deviation and absolute accuracy in the low centimeter range, even in challenging multipath environments. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEH.anultr

Basics of Wireless Local Positioning - Vossiek, Martin; Ebelt, Randolf (IEEE IMS Workshop on Innovative and Highly Accurate Local Positioning Systems, IEEE International Microwave Symposium 2011 (IMS2011), 2011)
lhft_intern.bib::Vossiek2011

Cooperative Indoor Localization Using 24-GHz CMOS Radar Transceivers - Ebelt, Randolf; Hamidian, Amin; Shmakov, Denys; Zhang, Tao; Subramanian, Viswanathan; Boeck, Georg; Vossiek, Martin (IEEE Transactions on Microwave Theory and Techniques, 2014)
This paper presents the first truly wireless 24-GHz round-trip time-of-flight local positioning frontend with an integrated CMOS transceiver. The transceiver in 130-nm CMOS technology features a novel receiver/transceiver switching concept, which reduces RF losses between the receiver/transmitter and antenna and drastically improves the transmit/receive isolation. The low-power RF transceiver chip was integrated with a digital signal-processing unit and mounted on a circuit board to form a system-level demonstrator of a secondary radar node incorporating synchronization and a distributed localization algorithm. The performance of the self-organizing localization network is evaluated in an indoor setup using comparisons with reference trajectories. Experimental results show a distance precision between the active nodes close to the theoretical optimum that can be achieved with the used signal parameters, as well as an absolute localization error in the centimeter rang
lhft_intern.bib::Ebelt2014a

Design of an Optimized Linear Sparse Antenna Array for a 24 GHz Radar Tachymeter - Pavlenko, Tatiana; Reustle, Christoph; Thurn, Karsten; Shmakov, Denys; Ebelt, Randolf; Vossiek, Martin (2015)
This paper presents the design of a linear antenna array for use in a 24 GHz radar tachymeter. The task of the proposed radar tachymeter is the precise measurement of the distance and angle to a cooperative transponder. To obtain the desired high accuracy, we designed an optimized sparse antenna array. The antenna pattern was selected using a brute-force optimization method. A fixed number of array elements was placed on a limited number of allowed grid positions and the array pattern with the best figure of merit for the given radar tachymeter application was selected. This approach can be successfully employed for sparse antenna array designs where multiple constraints such as aperture size limitations or number and spacing of antenna array elements are given. Distance and angle measurements taken with the implemented optimized array show excellent results. The standard deviations in range and azimuth were 8.6 mm and 0.1°, respectively for a range of several hundred meters.

Ein Mikrowellensensornetzwerk zur räumlichen Fahrzeug-zu-Fahrzeug- und Fahrzeug-zu-Infrastruktur-Ortung (A Wireless Sensor Network for Spacial Vehicle-to-vehicle and Vehicle-to-infrastructure Localization) - Ebelt, Randolf; Millner, Hendrik; Vossiek, Martin (Technisches Messen, 2010)
lhft_intern.bib::Ebelt2010

Funkbasierte 3D-Lokalisierung von Tieren zur Verhaltensanalyse im Innen- und Außenbereich - Ebelt, Randolf; Millner, Hendrik; Hoffmann, Gundula; Vossiek, Martin (Radio Techniques and Technologies for Commercial Communication and Sensing Applications, RadioTecC 2009, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.funkba

Funkbasierte Netzwerk-zu-Netzwerk-Ortung zur Bestimmung der Position und Orientierung von Fahrzeugen - Ebelt, Randolf; Vossiek, Martin (FAM-Workshop Navigation und Lokalisierung, 2011)
lhft_intern.bib::Ebelt2011a

Identification of Ghost Moving Detections in Automotive Scenarios with Deep Learning - Martinez Garcia, Javier; Prophet, Robert; Fuentes, Michel Juan Carlos; Ebelt, Randolf; Vossiek, Martin; Weber, Ingo (IEEE MTT-S International Conference on Microwaves for Intelligent Mobility (ICMIM 2019), 2019)
We introduce a method to classify ghost moving detections in automotive radar sensors for advanced driver assistance systems. A fully connected network is used to distinguish between real and false moving detections in the occupancy gridmaps. By using this architecture, we combine the local Doppler information, along with the spatial context of the surrounding scenario to classify the moving detections. A proof of concept experiment shows promising results with data from a test drive in an urban scenari

Instantaneous Ghost Detection Identification in Automotive Scenarios - Prophet, Robert; Martinez Garcia, Javier; Fuentes, Michel Juan Carlos; Ebelt, Randolf; Vossiek, Martin (Radar Conference 2019, Boston (MA), USA, April 2019, 2019)
This paper addresses one of the most serious drawbacks of automotive radar sensors: The frequent occurrence of ghost detections. As such detections may cause undesired behavior, they need to be partially or completely eliminated. We present an algorithm, which uses a machine-learning-based classifier to distinguish between real and ghost detections. In contrast to other papers, this approach addresses all causes of ghost detections and not only simple multipath scenarios. Real world experiments – also in challenging situations – show success rates of 91

Moeglichkeiten und Grenzen zur FMCW-Radar basierten Ortung von Backscatter RFID-Tags in Umgebungen mit stark gestoerten Mehrwege-Kanälen - Ebelt, Randolf; Li, Gang; Vossiek, Martin (RADCOM 2011 - Workshop, Developer Forum and Exhibition, 2011)
lhft_intern.bib::Ebelt2011b

Neue Ansätze für die verteilte kooperative räumliche Lokalisierung in drahtlosen Sensornetzwerken - Ebelt, Randolf (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)
UnivIS-Import:2016-07-26:Pub.2014.tech.IE.LEH.neuean

Noise in homodyne FMCW radar systems and its effects on ranging precision - Thurn, Karsten; Ebelt, Randolf; Vossiek, Martin (IEEE International Microwave Symposium 2013, 2013)
In this paper, a closed-form expression for the ranging uncertainty of a primary frequency-modulated continuous-wave (FMCW) radar is introduced. In addition to basic system parameters also the phase noise profile of the transceiver serves as an input for this novel approach. On the signal processing side, phase noise range correlation effects are taken into account and an estimate for the ranging uncertainty is deduced. Thus, the influence of phase noise on the system performance in terms of precision can be directly predicted. For support of the theory, Monte-Carlo simulations were conducted. Measurement results acquired with a 77 GHz radar system are in good agreement with the theory. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.noisei
Keywords: Frequency modulation; Millimeter-wave radar; Phase locked loop; Phase noise; Remote sensing; Signal synthesis

On the performance of pulsed frequency modulated UWB local positioning systems - Ebelt, Randolf; Waldmann, Benjamin; Bauer, Georg; Aleksieieva, Anna; Eßwein, Alexander; Weigel, Robert; Vossiek, Martin (2011 IEEE MTT-S International Microwave Symposium, IMS 2011, 2011)
Recently, a novel ultra-wideband (UWB) local positioning concept based on pulsed frequency modulated (PFM) signals was introduced by the research groups of the authors of this paper. The current paper presents a detailed analysis of the performance - i.e. range and accuracy - of the proposed PFM-UWB approach. It is shown that with PFM-UWB an excellent coverage/range can be achieved. It is also shown that for high precision ranging a VCO with good phase-noise performance is needed. Based on simulations and measurement results the theoretical findings are verified. The results confirm that PFM-UWB allows for accuracy in the mm-range and a maximum range of more than 100 m with a measuring time of only 1 ms. © 2011 IEE
Keywords: radar; radio navigation; radio position measurement; transponders; Ultra-wideband (UWB)

Particle Filter Based Synthetic Aperture Reconstruction Approach for Real-Time 3D Wireless Local Positioning - Li, Gang; Ebelt, Randolf; Vossiek, Martin (7th German Microwave Conference (GeMiC2012), 2012)
In this paper we introduce a precise real-time 3D indoor localization concept using a combination of the MISAS (multilateral inverse synthetic aperture secondary radar) approach and particle filtering. The synthetic aperture approach is a promising locating technique with effective multipath suppression. However, the practical usage in real-time applications is limited by its huge computational load of conventional SAR reconstruction algorithms. Instead of evaluating the PDF (probability density function) of the target position in a grid-based approach, we utilize a set of weighted particles to represent the PDF. The particle number can then subsequently be reduced in the following iterations through a resampling algorithm. It is shown by simulation and experiments with a 5.8 GHz FMCW secondary radar with 140 MHz bandwidth, that 3D localization of a robot TCP (tool center point) in mm-range with a few hundred particles is possible even in a dense multipath environment. With our new approach the computational effort has been reduced to below 0.1% compared to a grid-based evaluation. Therefore, this novel extension of particle filtering gives an attractive solution for the real-time application of 3D MISAS localization. © 2012 Institut f r Mikrowellen.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEH.partic
Keywords: FMCW secondary radar; indoor wireless positioning; multilateral inverse synthetic aperture secondary radar; particle filter

Where is the Tag? - Miesen, Robert; Ebelt, Randolf; Kirsch, Fabian; Schäfer, Tobias; Li, Gang; Wang, Haowei; Vossiek, Martin (IEEE Microwave Magazine, 2011)
Radio-frequency identification (RFID) localization developments and trends are reviewed. RFID localization relative to a reader can be broken down into two different tasks: ranging and direction finding. A system with both of these capabilities can provide two-dimensional (2-D) or three-dimensional (3-D) localization and an RFID system with only one of these capabilities can still provide useful functionalities. Standard RFID systems feature only coarse locating capabilities with a granularity given by the dimension of a cell formed by a reader. RFID ranging techniques may be categorized according to three criteria. The first and second are the type of transponder and the fundamental principle behind tag localization. Broadband chipless RFID tags have emerged as very promising candidates for next generation locatable RFID transponder
lhft_intern.bib::Miesen2011c

Wireless 3D-localization of animals for trait and behavior analysis in indoor and outdoor areas - Millner, Hendrik; Ebelt, Randolf; Vossiek, Martin; Schlender, Kristin; Hoffman, Gundula (IEEE MTT-S International Microwave Workshop on Wireless Sensing, Local Positioning, and RFID, 2009)
This paper describes a system for three dimensional indoor and outdoor localization of animals using a sequential Monte-Carlo-Method. A Kaiman based particle filter is used to improve the measurement quality by incorporating the dynamics of the target object. The positioning method was integrated into a system for animal behavior analysis which provides extensive features to identify habitual residence and movement patterns of the animals. © 2009 IEEE.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.wirele
Keywords: Animal localization; Positioning; Real-time location; Sequential Monte Carlo methods

Wireless Sensor Network with 24 GHz Local Positioning Transceiver - Shmakov, Denys; Ebelt, Randolf; Vossiek, Martin (IEEE MTT-S International Microwave Symposium 2012 (IMS 2012), 2012)
This paper reports on an innovative cooperative wireless localization network layout and the design of its network nodes. Each node consists of a 24 GHz FMCW secondary radar for bilateral range measurements between all nodes. Network synchronization and scheduling is based on IEEE 802.15.4 radio units. A novel concept to distributedly pre-synchronize all network nodes with an error of less than 125 ns was implemented and combined with the 24 GHz local positioning radar. With prototypes of the sensor nodes a ranging precision of about 1 cm is demonstrated experimentally. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEH.wirele
Keywords: FMCW; IEEE 802.15.4; Secondary radar; Sensor network; Time synchronization